Downshifted peak features of stimulated electromagnetic emissions during a two-pump wave heating experiment. Issue 7 (1st October 2019) - Ma, Guanglin; Guo, Lixin; Li, Qingliang; Yang, Jutao; Lv, Libin; Chen, Jing; Xu, Tong; Hao, Shuji; Wu, Jian
Abstract: Experimental results of the downshifted peak (DP) in stimulated electromagnetic emissions under two-pump wave ionospheric heating near the third electron gyroharmonic frequency are presented. The European Incoherent Scatter Scientific Association heating antenna array was divided into two parts, one of which worked at constant pump wave frequency f 1 and the other part worked at varied pump wave frequency f 2 which was not larger than f 1 . It was found that when the second pump wave was turned on at different frequency with f 1, the f 1 DP power declined by more than 10 dB with respect to the background noise level, while the downshifted maximum belonging to f 1 was further enhanced. The time needed to reach a steady state for DP was shortened from approximately 10 s under cold background conditions belonging to f 1, which was nearly consistent with growth time of small-scale artificially field-aligned irregularity (AFAI), to less than 1 s under the preconditioned heating belonging to f 2 with pre-existing AFAI. According to the difference in DP temporal evolution under two experimental conditions, it could be deduced that AFAI plays an important role in the DP generation process. Similar to single-pump wave heating, the frequency offset of DP decreases as f 2 increases toward the third electron gyroharmonic frequency. These experimental findings provide new insights into the theoretical study of ionospheric plasma nonlinearity.